The evaluation on the performances of a roundabout at Taman Tas, Kuantan - Khairun Nadrah, Hamidzon (2012)
At present, smooth movement on the roads is something that is needed for each user. Many roads, especially in urban areas will be upgraded because of the number of vehicles increase from time to time. So, it very important to monitor and analyze traffic congestion that can be enhanced using either the performance of traffic lights, geometry change, and others. This study is about the performance of roundabout at Jalan Tas 4, Taman Tas, Kuantan where the original type of road is unsignalized four leg intersection. In this project, Sidra Intersection 5.1 software is used to determine the effectiveness of roundabout in term of capacity of roundabout, delay and queue and level of service of roundabout. Before using Sidra Intersection 5. 1, the data recorded two times on morning peak hour and evening peak hour. After the traffic flow and geometry of roundabout are taken, the data is analyzed using Sidra Intersection 5.1 and the result from the process data in term of capacity, delay, queue, and level of service for each movement on each approach are given. The output data from Sidra Intersection 5.1 is in term of graphic and text. The graphic data especially for level of service and delay is in colorful graphic to differentiate the good performance and poor performance. In this study, the recommendation for the problem at roundabout is also given. T he recommendation is to increase the size of central island to 10 m since the area is limited area. By enlarging the diameter of central island, the same data is used to analyze the performance of proposed diameter by using Sidra Intersection 5.1. From the output data, there is improvement of performance of Eoundabout at Taman Tas, Kuantan in term of delay, queue and capacity.